Study of the fungal decay of oil palm wood using TEM and UV techniques. (July 2016) - Schmidt, Olaf; Bahmani, Mohsen; Koch, Gerald; Potsch, Tanja; Brandt, Karin
Abstract: Oil palm wood samples were subjected to decay by the brown-rot fungus Coniophora puteana and the white-rot species Pleurotus ostreatus . There was up to 61% mass loss by C. puteana and 32% by P. ostreatus within two month of incubation. Light microscopy of the decayed samples showed preferential degradation of the parenchymatous ground tissue and phloem in the vascular bundles. Transmission electron microscopy revealed details on the micromorphology of cell wall decay. C. puteana consumed the carbohydrates. P. ostreatus produced simultaneous white-rot. Ultraviolet microspectrophotometry provided insight in lignin degradation by P. ostreatus showing lignin decrease in the walls of parenchyma cells, fibers and vessels. C. puteana increased the UV absorbance due to depolymerization of the lignocelluloses matrix and modifications in the lignin side chains.